Optical coherence tomography‐based angiography device with real‐time angiography B‐scans visualization and hand‐held probe for everyday clinical use. Issue 10 (5th July 2018) - Moiseev, Alexander; Ksenofontov, Sergey; Sirotkina, Marina; Kiseleva, Elena; Gorozhantseva, Maria; Shakhova, Natalia; Matveev, Lev; Zaitsev, Vladimir; Matveyev, Alexander; Zagaynova, Elena; Gelikonov, Valentin; Gladkova, Natalia; et al.
Abstract : This work is dedicated to the development of the OCT system with angiography for everyday clinical use. Two major problems were solved during the development: compensation of specific natural tissue displacements, induced by contact scanning mode and physiological motion of patients (eg, respiratory and cardiac motions) and online visualization of vessel cross‐sections to provide feedback for the system operator. Abstract : This work is dedicated to the development of the OCT system with angiography for everyday clinical use. Two major problems were solved during the development: compensation of specific natural tissue displacements, induced by contact scanning mode and physiological motion of patients (eg, respiratory and cardiac motions) and online visualization of vessel cross sections to provide feedback for the system operator. Visualization of oral mucosa microvasculature with the proposed technique.